2016
DOI: 10.1002/cb.1597
|View full text |Cite
|
Sign up to set email alerts
|

Youth and the sociability of “Vaping”

Abstract: This article examines the contemporary and evolving social ritual of vaping (also known as the use and consumption of e-cigarettes). This novel research finds a typology of users in a heterogeneous youth market and shows how the introduction of this new practice challenges existing ritual boundaries. Previous research has focused on the de-marketing of tobacco and smoking cessation. Here, virtuous, dynamic, vulnerable, and invisible vapers are identified with each demonstrating differing levels of emotional en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 63 publications
3
34
0
Order By: Relevance
“…All dual and triple substance combinations including this behaviour rose in prevalence towards the end of the examined period, with concurrent vaping and drinking particularly common. The association between e-cigarettes and alcohol, previously observed in other studies ( Morean et al, 2016 ; Schlienz & Lee, 2018 ; Taylor et al, 2017 ), together with data on social media trends ( Camenga et al, 2018 ; Chu et al, 2018 ; Sampasa-Kanyinga & Hamilton, 2018 ), indicates that use of the former is now a social activity ( Pepper et al, 2017 ; Yule & Tinson, 2017 ). This is particularly concerning not only in light of potential feedback effects due to the previously discussed outsize effects of peer behaviour, but also because e-cigarette use has been shown to increase the risk of cigarette smoking ( Barnett et al, 2015 ; Bold et al, 2018 ; Hammond et al, 2017 ), which also often co-occurs with alcohol use in social situations ( Berg et al, 2018 ; Gubner, Thrul, Kelly, & Ramo, 2018 ; Silveira et al, 2018 ), adding an additional layer of risk.…”
Section: Discussionsupporting
confidence: 60%
“…All dual and triple substance combinations including this behaviour rose in prevalence towards the end of the examined period, with concurrent vaping and drinking particularly common. The association between e-cigarettes and alcohol, previously observed in other studies ( Morean et al, 2016 ; Schlienz & Lee, 2018 ; Taylor et al, 2017 ), together with data on social media trends ( Camenga et al, 2018 ; Chu et al, 2018 ; Sampasa-Kanyinga & Hamilton, 2018 ), indicates that use of the former is now a social activity ( Pepper et al, 2017 ; Yule & Tinson, 2017 ). This is particularly concerning not only in light of potential feedback effects due to the previously discussed outsize effects of peer behaviour, but also because e-cigarette use has been shown to increase the risk of cigarette smoking ( Barnett et al, 2015 ; Bold et al, 2018 ; Hammond et al, 2017 ), which also often co-occurs with alcohol use in social situations ( Berg et al, 2018 ; Gubner, Thrul, Kelly, & Ramo, 2018 ; Silveira et al, 2018 ), adding an additional layer of risk.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, individuals that strongly identify with smoking groups are more likely to resist antismoking campaigns [ 44 ]. Similar to smoking, e-cigarettes allow youth to form a community based on the inclusion criteria of vaping, which enables opportunities for increasing social networks and establishing a group identity [ 45 , 46 ]. Narratives of social identity and belonging around e-cigarette use have a powerful impact on youth, not only for shaping positive attitudes around vaping but also for resisting prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term e-cigarette use has been shown to deliver similar reductions in levels of measured carcinogens and toxins relative to smoking only combustible cigarettes as NRT (Shahab et al, 2017) and government regulations are intended to ensure e-cigarette minimum safety and efficacy standards (European Commission, 2014; MHRA, 2016). Vaping cultures have previously been identified among youth (Yule & Tinson, 2017). A study in a disadvantaged area of England found a culture of vaping only among young men (Thirlway, 2016) who had time and resources to find e-cigarettes that suited them.…”
Section: Discussionmentioning
confidence: 99%